Carfilzomib for treating myeloma - Ziogas, D.C.; Terpos, E.; Kastritis, E.; Dimopoulos, M.A. (Expert Opinion on Orphan Drugs, 2016)
Introduction: Carfilzomib, a second-generation proteasome inhibitor, has been increasingly used in relapsed/refractory multiple myeloma (MM) since its initial approval by the Food and Drug Administration in 2012, either as a single agent or in combination with other known anti-myeloma treatments. Based on its efficacy and safety profile in the relapsed/refractory setting, carfilzomib is currently evaluated in patients with de novo MM. Areas covered: Here, we will shed some light on the introduction of carfilzomib as an effective anti-myeloma treatment, presenting its mechanism of action, its response rates and adverse events, as well as a summary of all clinical trials evaluating current dosage and schedule of administration. We will follow the entire path of drug’s development from the bench of preclinical studies to the market and bedside delivery. Revising the published evidence, we will try to answer all questions raised about the novel drug, expressing in parallel our site experience. Expert opinion: Carfilzomib, alone or in combination with other agents, is a welcome therapeutic option for MM patients with a well-defined toxicity profile. Results of ongoing trials are expected in order to update drug indications and maximize its therapeutic benefits in patients with refractory/relapse MM. © 2016 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Carfilzomib; multiple myeloma; newly diagnosed; proteasome inhibitor; relapsed/refractory